Evaluation and analysis of traffic flow at signalized intersections in Nicosia using of SIDRA 5 software - Ali, Shaban Ismael Albrka; Reşatoğlua, Rifat; Tozan, Hudaverdi (Penerbit Universiti Kebangsaan Malaysia, 2018)
Traffic congestion on road networks and signalized intersections have posed significant problems worldwide. One of the significant ways to reduce traffic congestion in cities is by improving the public transportation system. Therefore, it is essential to use advanced software tools to ensure that the current system can be controlled and evaluated. This study was aimed at assessing and analysing the performance of traffic flow at signalized intersections and roundabouts at peak hours in the city of Nicosia (northern part of the island) using the SIDRA INTERSECTION 5 software. It was also aimed at comparing the performance of traffic flow during the morning and evening peak hours at four intersections and two roundabouts. The parameters used to assess the performance of the traffic flow were the level of service, delays and delayed travel speed, performance index, operating cost, fuel consumption, and carbon dioxide emission. It was found that the SIDRA INTERSECTION software was able to give an estimate of the current situation of traffic flow in the city. The results showed that the level of service was low, resulting in low speeds and lots of delays during the evening and morning peak hours. The delay was up to 9318.9 seconds and the fuel consumption was nearly 1431.6 lit/h, while the CO2 emission was up to 3594.7 kg/h.